104 Match congestion and training load influence injury risk in collegiate men's and women's soccer. (3rd March 2020) - Huggins, Robert; Curtis, Ryan; Benjamin, Courteney L; Sekiguchi, Yasuki; Wasserman, Erin; Klossner, David; Casa, Douglas J
Abstract : Background: Optimal recovery between collegiate soccer matches and the influence of training load (TL) on injury rate (IR) is unknown. Objective: To examine the influence of days rest and increases in TL between matches on injury rate (IR), RR and odds of injury. Design: Prospective multi-site study. Setting: NCAA division I men's and women's soccer. Participants: Twelve teams, (men=132; women=139). Assessment of risk factors: Days between matches, daily exposures, TL and injury data were tracked daily. Main outcome measurements: Overall, acute non-contact (NC) and NC-overuse IRs expressed per 1000 athlete exposures (AEs), RR and odds ratios (OR) were determined. Associations between injury and changes in TL were analyzed using a multilevel logistic regression. Results: Match IR (per 1000AEs [95% CI]) was 47.9 [39.1, 56.6] in men and 39.0 [31.1, 46.9] in women. Odds of being injured in a match with 1–5 vs. 6+ days rest was increased in men (OR [95% CI] 1.93 [1.15, 3.23] (p=0.01) and women (1.79 [1.02, 3.17] p=0.04). Preseason injury rates were 2.11 and 1.68 times higher than the seasonal average rates for men (26.8/1000 AE vs. 12.7/1000 AE) and women (28.8/1000 AE vs. 17.1/1000 AE). In women, acute NC IR in matches with 1–3 vs. 4+ days' rest were elevated (RR=3.01 [1.11, 8.14] p=0.03). NC-overuse IR in women during matches were elevated for both 1–3 vs. 4+ and 1–5 vs. 6+ days rest (RR=2.24 [1.03, 4.88) p=0.05; 7.85 [1.06, 57.94] p=0.04). No differences in RRs exit between matches for starters in both men and women. In men, for each additional 3500m covered on a session and each additional 60 min of training, odds of NC-overuse injury increased 1.70 [1.38, 2.10] and 1.83 [1.59, 2.12]. In women, for each additional 3000m covered on a given session, odds of overall injury increased 1.41 [1.24, 1.60] and for each additional 45 min played acute NC odds increased 1.51 [1.12, 2.03]. Conclusions: These findings suggest the current structure and TL may be putting players at increased risk for injury. These data should be used to guide the NCAA in determining optimal scheduling and recovery for injury prevention.